A Ten-N6-Methyladenosine (m6A)-Modified Gene Signature Based on a Risk Score System Predicts Patient Prognosis in Rectum Adenocarcinoma - Huang, Wei; Li, Gen; Wang, Zihang; Zhou, Lin; Yin, Xin; Yang, Tianshu; Wang, Pei; Teng, Xu; Feng, Yajuan; Yu, Hefen (Frontiers in Oncology, 2021)
The study aims to analyze the expression of N 6 -methyladenosine (m 6 A)-modified genes in rectum adenocarcinoma (READ) and identify reliable prognostic biomarkers to predict the prognosis of READ.RNA sequence data of READ and corresponding clinical survival data were obtained from The Cancer Genome Atlas (TCGA) database. N 6 -Methyladenosine (m 6 A)-modified genes in READ were downloaded from the "m 6 Avar" database. Differentially expressed m 6 A-modified genes in READ stratified by different clinicopathological characteristics were identified using the "limma" package in R. Protein-protein interaction (PPI) network and co-expression analysis of differentially expressed genes (DEGs) were performed using "STRING" and Cytoscape, respectively. Principal component analysis (PCA) was done using R. In addition, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathways were used to functionally annotate the differentially expressed genes in different subgroups. Univariate Cox regression analyses were conducted to identify the powerful independent prognostic factors in READ associated with overall survival (OS). A robust likelihood-based survival model was built using the "rbsurv" package to screen for survival-associated signature genes. The Support Vector Machine (SVM) was used to predict the prognosis of READ through the risk score of survival-associated signature genes.We screened 974 differentially expressed m 6 A-modified genes among four types of READ samples. Two READ subgroups (group 1 and group 2) were identified by consensus clustering according to the expression of DEGs. The two subgroups were significantly different in overall survival and pathological stages. Next, 118 differentially expressed genes between the two subgroups were screened and the expression of 112 genes was found to be related to the prognosis of READ. Next, a panel of 10 survival-associated signature genes including ADAMTSL1, CSMD2, FAM13C, FAM184A, KLHL4, OLFML2B, PDZD4, SEC14L5, SETBP1, TMEM132B was constructed. The signature performed very well for prognosis prediction, time-dependent receiver-operating characteristic (ROC) analysis displaying an area under the curve (AUC) of 0.863, 0.8721, and 0.8752 for three-year survival rate, prognostic status, and pathological stage prediction, respectively.A-modified genes that may be involved in the pathophysiology of READ and constructed a novel gene expression panel for READ risk stratification and prognosis prediction.